Determinants of sheep husbandry practice: the case of Mihur Aklil District, Gurage Zone, SNNPR, Ethiopia - Tarekegn Derbib; Bezalem Sinote (Journal of Applied Animal Research)
The objective of this study was to identify the main determinants of sheep husbandry practices in Mihur Aklil District Gurage Zone Ethiopia under a smallholder farmer’s management system. The agroecology was stratified systematically into highland and midland. The study Kebeles were selected randomly whereas purposive sampling technique was used to select a total of 240 households from two agro-ecologies. Household surveys, key informant interviews and focus group discussions were employed to draw data. Multiple linear regression models were used to identify the major factors that determine husbandry practices with management index. The multiple linear regression analysis indicated that the major determinant factors that affect sheep husbandry practices were landholding size (0.6), household size (0.65), farmer’s participation in training (0.5), total livestock unit (−1.25), availability of improved forage (0.826), infrastructure (1.3) and fattening for seasonal market (−0.4). Accordingly, landholding size, household size, training, availability of improved forage and infrastructure, were positive determinants of sheep husbandry practice, while total livestock unit and fattening for seasonal market were negatively determining sheep husbandry practice in the study area. The study implies that strengthening effective training services, land utilization, enhancing availability improved forage and basic infrastructures would improve sheep husbandry practice of smallholder farmers.